2017
DOI: 10.1016/j.pec.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Does the quality of safetalk motivational interviewing counseling predict sexual behavior outcomes among people living with HIV?

Abstract: Objective Although past research has demonstrated a link between the quality of motivational interviewing (MI) counseling and client behavior change, this relationship has not been examined in the context of sexual risk behavior among people living with HIV/AIDS. We studied MI quality and unprotected anal/vaginal intercourse (UAVI) in the context of SafeTalk, an evidence-based secondary HIV prevention intervention. Methods We used a structured instrument (the MISC 2.0 coding system) as well as a client-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…There was no evidence found in support of the relational pathway of MI within the context of improving ART adherence levels; namely change talk (or sustain talk) was not found to mediate the relationship between MI spirit and ART adherence. This result is consistent with findings reported in a meta-analysis [25], although an association between MI spirit and fewer instances of unprotected anal/vaginal intercourse has been reported in people with HIV [27]. Baseline rates were not controlled for in this study, however.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was no evidence found in support of the relational pathway of MI within the context of improving ART adherence levels; namely change talk (or sustain talk) was not found to mediate the relationship between MI spirit and ART adherence. This result is consistent with findings reported in a meta-analysis [25], although an association between MI spirit and fewer instances of unprotected anal/vaginal intercourse has been reported in people with HIV [27]. Baseline rates were not controlled for in this study, however.…”
Section: Discussionsupporting
confidence: 92%
“…Pre-session MI adherence levels were measured and were used in the mediational models as either a covariate or to create a difference score. The sample size was larger than other published MI process research studies within the context of HIV-related behaviour change [26,27]. The sample size was also large enough to make it unlikely that null findings (often associated with small effects) were due to a lack of statistical power.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research suggests that MI quality is often a significant predictor of behavior change; in the SafeTalk intervention, participants whose counselors received higher MI quality ratings were less likely to report unprotected sex at 8-month follow-up. [36] In the sub-Saharan African setting, Evangeli et al found that counselors trained for 12 hours in MI for a range of HIV-related health behaviors reported high levels of confidence in providing MI, but had not achieved beginning proficiency by the end of the training[27] or one year later. [28] The importance of MI quality and the number of counselors failing to achieve proficiency in Evangeli's studies suggest that further research is needed on the ability of counselors to achieve MI proficiency in sub-Saharan African settings.…”
Section: Discussionmentioning
confidence: 99%
“…If MI works as hypothesized, by conveying a relational and technical component (Miller and Rose, 2009), there should be clear associations between the fidelity of these elements and client outcomes. Although MI therapist behaviors are commonly linked to outcomes in studies of MI (Borsari et al, 2015;Gaume et al, 2014;Gaume, Heather, Tober, and McCambridge, 2018;Grodensky et al, 2017), meta-analyses of this hypothesized association have not detected direct associations between MI elements and outcome (Magill et al, 2018;Pace et al, 2017). Indications were found, T however, for indirect pathways of associations between MI-elements and outcome; that is, through measures of client change talk or client sustain talk leading to change outcomes.…”
Section: Fidelity and Outcomementioning
confidence: 96%